(3EUMGMGJ GdbOjS eJis - (3GdbOjS eJjs
(3ChdgG (B:s
(3fHJOF HYhf Gddg hMSf Jhajbg hEQTGOg fcJH GdCQHYI CfGLjd GdebOSI GdChd ef Pdc HTGQI GdbOjS eJi GdEfLjdi Chd bQGAg efg djhe GdCMO bHd GdejdGO GdeLjO cJGH ehdO EjShY GdeSjM GHf OGhO s
(3BNQgG (B:s
(3EQMefG jG QH HTaGYI JdGejPc hQSdc GdCWgGQ ai LhgQkG dGjfbSe s
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdOjGfGJ GdCNQis